Ultra-broadband and omnidirectional enhanced absorption of graphene in a simple nanocavity structure. (November 2016) - Lee, Yang-Chun; Lin, Keng-Te; Chen, Hsuen-Li
Abstract: In this study, we developed a simple approach, using a nanocavity structure, to increase the light absorption of graphene in an ultra-broadband and omnidirectional manner. We determined the light absorption of graphene by calculating the surface electric fields (E-fields) of various underlying substrates. Although the surface E-field was maximized for both one-dimensional photonic crystals and a metal/dielectric nanocavity structure, the much simpler two-layer nanocavity configuration also provided ultra-broadband and omnidirectional enhancement of absorption. By selecting a suitable metal as the back reflector and controlling the thickness of the single-layer dielectric spacer in the nanocavity structure, we found experimentally that the light absorption of graphene could be enhanced approximately fivefold, with full widths at half maximum of 200 nm in the ultraviolet, 400 nm in the visible, and greater than 1000 nm in the infrared regime. Moreover, we observed a significantly enhanced photo–heat response from the greater light absorption of graphene in the nanocavity structure. The absorbance spectrum of graphene in the nanocavity structure perfectly matched the air mass 1.5 solar spectrum, suggesting that such systems might be very useful for harvesting solar energy in optoelectronic devices.